The Risk of Nephropathy, Retinopathy, and Leg Amputation in Patients With Diabetes and Hypertension: A Nationwide, Population-Based Retrospective Cohort Study - Yen, Fu-Shun; Wei, James Cheng-Chung; Shih, Ying-Hsiu; Hsu, Chih-Cheng; Hwu, Chii-Min (Frontiers in Endocrinology, 2021)
Purpose: To compare the risks of chronic kidney disease (CKD), end-stage renal disease (ESRD), sight-threatening retinopathy, and leg amputation between patients with DM or HTN. Methods: From January 1, 2000, to December 31, 2015, we identified 28943 matched pairs of patients with DM with and without subsequent HTN, 89102 pairs of patients with HTN with and without subsequent DM, and 145294 pairs of patients with coexisting DM and HTN with a previous history of DM or HTN from Taiwan’s National Health Insurance Research Database. Cox proportional-hazard models were used for calculating the risks of CKD, sight-threatening retinopathy, and leg amputation. Results: The mean follow-up time of this study in different cohort was between 3.59 and 4.28 years. The adjusted HRs (95% CIs) for CKD, ESRD, sight-threatening retinopathy, and leg amputation in DM patients with and without subsequent HTN, HTN patients with and without subsequent DM, and comorbid DM and HTN patients with previous DM and with previous HTN were 2.77 (2.61-2.94), 1.73 (1.68-1.77), and 1.04 (1.02-1.07); 42.38 (22.62-79.4), 2.76 (2.43-3.13), and 0.72 (0.66-0.79); 2.07 (1.85-2.3), 3.41 (3.14-3.71), and 1.51 (1.43-1.58); and 4.74 (3.02-7.43), 6.27(4.72-8.31), and 1.19(1.03-1.38), respectively. Conclusions: This nationwide cohort study demonstrated that patients with DM and subsequent HTN and patients with HTN and subsequent DM showed significantly higher risks of incident CKD, ESRD, sight-threatening retinopathy, and leg amputation.